BACTERIOLOGY AND PROXIMATE COMPOSITION OF UGBA FROM MINNA MARKET AFTER PROLONGED FERMENTATION - ABDULLAHI, MOHAMMED; MUHAMMAD, 2MUHAMMAD; MOHAMMED, SULAIMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Different fermentation time are used in production of varieties of Ugba. This affects bacteriological and nutritional quality of this popular and much preferred fermented food product in Nigeria. In this study, 10 Ugba samples collected from Minna market were further fermented for 2 days in the laboratory. Bacteriology and proximate composition of the laboratory fermented sample was evaluated and compared to unfermented original Ugba sample. Total bacterial count ranged from 63.00×104 CFU/g in laboratory fermented Ugba and 39.00×104 CFU/g in the Original unfermented samples. Proximate composition showed 53.61±0.01 % – 38.87±1.18 % Moisture, 2.26±0.14% – 2.4±0.22% Ash, 5.01±0.17% – 6.03±0.57 % Fat, 1.93±0.46% – 2.89±0.06 % Fibre, 27.37±1.18% – 23.15±1.31% Protein and 9.81±1.62% – 26.65±0.52% Carbohydrate in fermented and unfermented Ugba samples respectively. Bacterial load was higher in the fermented sample compared to original sample and Bacillus species identified the most occurring bacterial. Other less populated bacteria identified are Escherichia coli, Pseudomonas, Streptococcus and Klebsiella species. Proximate analysis revealed significant increase in moisture, protein contents and a decrease in carbohydrate with increased fermentation time. Prolonged fermentation increases the protein content of Ugba but enhances contamination and rapid spoilage.